Актуальні аспекти управління активами комерційних банків - Тужиліна, С.О.; Фролов, В.І. (Культура народов Причерноморья, 2013)
У статті наведено визначення поняттям «активи комерційного банку» та «активні операції комерційного банку». Розглянуто основи управління активами комерційного банку в сучасних умовах. Проведено аналіз обсягів активних операцій комерційних банків України за 2010-2012 роки та зроблені відповідні висновки. Проаналізовано методику управління активами на прикладі ПАТ КБ «ПриватБанк», що є одним з провідних банків України. Виявлені основні проблеми та напрямки реформування ресурсної бази вітчизняних комерційних банків. Ключові слова: активи, активні операції, управління активами, комерційний банк. В статье даны определение понятиям «активы коммерческого банка» и «активные операции коммерческого банка». Рассмотрены основы управления активами коммерческого банка в современных условиях. Произведен анализ объемов активных операций коммерческих банков Украины за 2010-2012 года и сделаны соответствующие выводы. Проанализирована методика управления активами ПАТ КБ «ПриватБанк», являющегося одним из ведущих банков Украины. Выявлены основные проблемы и направления реформирования ресурсной базы отечественных коммерческих банков. Ключевые слова: активы, активные операции, управление активами, коммерческий банк. This article provides definitions of such terms as «asset commercial bank» and «active operations of a commercial bank». It examines the basics of asset management of commercial bank in the present conditions of banks in Ukraine. The analysis of the volume of the active operations of commercial banks in Ukraine for 2010-2012 years and has drawn a conclusion according to the data . The article shows the main reasons for changes in the volume of the active operations of the banking system of Ukraine in recent years. Identified banks that are leaders in the industry. Analyzed the methods and principles of asset management on the example of Public Joint-Stock Company «PrivatBank», which is one of the leading banks in Ukraine. The analysis of the dynamics of the composition and structure of the active operations of the bank, as well as analysis of the loan portfolio. This is done with the purpose of finding profitable ways to improve the banking sector, based on the experience of successful banks. Also are revealed the main problems of the formation and direction of the reform of the resource base of domestic commercial banks. And thereafter examined the reasons of such a situation in the banking market at the moment. Conclusions are drawn with the current proposals for solving the existing problems in the commercial banks and the whole banking system of Ukraine. Keywords: commercial bank assets, the active operations of a commercial bank, asset management, commercial bank.